Noise assessment and control for industrial machine / Ab. Latif Main, Hannes Masandig and Saiful Bahri Bustami - Main, Ab. Latif; Masandig, Hannes; Bustami, Saiful Bahri (1994)
The work involved in this project are as follows: • To study the principle of noise control and the theory of sound. • To prepare the site according to International Standard (ISO 3746) requirement. • To gather sound level data from industrial machine i.e. the Air Compressor. • The machine shall be operated under two conditions:- • Idling • Full load. • To construct the spectrum graph using the data collected. • To design a noise enclosure. • To fabricate the noise enclosure. • To install the noise enclosure around the machine. • To record data of background noise as a basis of reference.